PESEARCH PROPERTIES OF THE CONTACT AREA BETWEENAND FINE CONCRETE - B.I. Saidmuratov,; H.A. Gulomovа, (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses properties in contact area of reinforcement with concrete and micro-reinforcement of fine sandy concrete with basalt fibers.